A natureza jurídica dos acordos de pesca - Guimarães, Ana Paula Fonseca Valadares (2012)
This research will examine the figure of the fisheries agreement as a management and regulation of the use of fishery resources, with the ultimate goal of identifying its legal status. For this and considering that the rules of fishing integrate local cultural norms (myths, taboos), as well as economic and political (patronage system, agreements) rules and external (government policy, market) (RUFINO, 2005) will address whether the institutional aspect encompassing preoccupation with the intensification of global environmental issues, to reach the Public Policies for the Fisheries sector, its development over the decades and the reshaping of the state apparatus. Alongside will be work on organization and social mobilization and empowerment to define and restrict access to fish resources in an attempt to serve the interests of the local population and the sustainability of the resource, as well as the reduction of conflict and pressure on resources. The research work dimensions normative, empirical and analytical theory of law, with a cross-sectional analysis, multidisciplinary whereas constitutive moment of legal experience not seize both the ideals of justice that men are inspired or inspiring to say, not so much the jurisdictions of incorporation, but the social reality in which the right way up and turns in the actions of men who make and unmake their behavior with the rules of conduct that govern them.